Wiedergabe von literarischen Vornamen in deutsch-polnischer Übersetzung (am Beispiel des Romans „Buddenbrooks” von Thomas Mann) - Pieciul, Eliza (Wydawnictwo Naukowe UAM, 2000)
The article discusses the question of the position of proper names (first names) in literary German-Polish translation. The empirical basis consists of first names from the novel by Thomas Mann (The Buddenbrooks) and its Polish translation. The first part of the article contains a theoretical introduction in the field of onomastics and discusses the nature and specific features of first names (1). In the next step different strategies of rendering of literary proper names are presented (2). The empirical analysis (3) shows the two main translation strategies: transcribing and adapting of literary first names, and their consequences for the target language reception. The article sums up the analysis of chosen first names presenting linguistic and cultural conditions for rendering of proper names in literary translation (4).